AN ANALYSIS OF TRANSLATION OF ARCHITECTURAL ENGINEERING TEXT FROM ENGLISH INTO INDONESIAN (A Case Study of the Second Semester Students of Architecture Engineering Department of Indonesia University of Education - Dini Herfiani, - (2008)
This research is entitled An Analysis of Translation of Architectural Engineering Textfrom English into Indonesian. Sincemost engineering books are written in English, this research is conducted to investigate the engineering students' translation procedures and their ability in translating English text into Indonesian related to Architecture Engineering accurately, clearly, and naturally. The research focuses on the analysis of translation products done by the subjects. The objectives of this research are to analyze translation procedures used by the subjects and to analyze students' ability in translating text from English into Indonesianrelated to ArchitectureEngineering. This research used qualitative descriptive methods to describe the quality of materials by using subjective points of view, and relationships of research elements. The respondents' translation products were analyzed by using translation procedures proposed by Newmark (1988). The results of this research show that the translation procedure commonly applied in students' translation is literal translation. In addition, naturalisation, couplets, synonymy, reduction and expansion, shift, equivalent, and modulation were also applied in their translation. Most students have not been able to translate English text into Indonesian related to Architecture engineering accurately, clearly, and naturally. The writer suggests that the students practice more in translating English text into Indonesian relatedto their field, learn translation theory to result in good translation, and studymore oflanguage grammar.